EDUCATIONAL INNOVATION TO REDUCE THE IMPACT OF THE COVID-19 PANDEMIC ON TEACHING THE PORTUGUESE LANGUAGE IN THE 8TH YEAR OF ELEMENTARY EDUCATION, IN A PUBLIC STATE SCHOOL IN MANAUS - Mendes Gandra, Heliana (Revista Gênero e Interdisciplinaridade, 2024)
This article aims to analyze the educational innovations developed by Portuguese language teachers in the final years of Elementary School, during the Covid 19 pandemic, and the difficulties faced by teachers in relation to the use of digital technologies in the pandemic context. In this sense, we developed qualitative research, of an exploratory nature, using as an instrument for data generation a form built, on the social network Whatsapp, for teachers from the state public network in the city of Manaus, capital of Amazonas. Furthermore, our analyzes point out the difficulties and innovations that teachers and students have suffered with the constant changes imposed by the remote teaching context with the coronavirus viral pandemic. The transformation scenario, caused by the Covid-19 pandemic, challenged both authorities and teachers in the public network of the state of Amazonas and, consequently, its capital Manaus, caused new reflections related to the use of digital educational resources to emerge in pedagogical planning. This research aims to analyze the educational innovations developed by Portuguese language teachers in Elementary School, during the Covid-19 pandemic. There was recurring concern among teachers, managers and pedagogues at all levels of education in the search for methods, techniques and activities capable of engaging students and promoting teaching appropriate to the online modality required. Despite the technological apparatus offered by the Department of Education and Sports, the joint action of students, parents and teachers, many challenges made teaching the Portuguese language difficult.